Instrumentos de qualificação ambiental para a recomposição da vegetação urbana: uma avaliação crítica diante das operações urbanas consorciadas - Sampaio, Vitor Hugo de Goes (2023)
This work considers the issues related to the growing suppression of vegetation cover and soil sealing in an urban environment. Its objective is to investigate the use of two environmental qualification instruments, specifically the Area Biotope Factor (BAF) and the Environmental Quota (QA), with the premise that this construct can mitigate the environmental impacts from the incorporation of green infrastructure rules at the urban lot scale. Its applications are empirically examined in urban areas subjected to physical interventions under the strong influence of the real estate market, which are a condition of Urban Consortium Operations (OUCs). The methodology adopted is qualitative and quantitative in nature and is based on geoprocessing techniques, remote sensing and field surveys. The OUCs Parque Foz Riacho Maceió (2000) and Lagoa do Papicu (2011), in the city of Fortaleza, are defined as a case study. First, the analysis rests on a review of the notions and concepts that gravitate around urban vegetation, such as green infrastructure and sustainability indicators for the interpretation of urban phenomena. In a second moment, the environmental results resulting from the implementation of OUCs are evaluated which indicate that, in the way it was executed, this urban policy does not meet the principles of environmental enhancement contained in the City Statute. Finally, the hypothetical scenario of BAF and QA application in these areas is considered to understand how these instruments can contribute to the improvement of urban areas, opposing the condition of flexibilization of land use and occupation. Under the moderation of the environmental qualification instruments analyzed here, it is possible to reduce the subjectivity of the counterparts required by the municipality and increase the idealization of projects integrated with nature in consolidated urban areas. It is hoped that this research will bring a contribution to the critical review of the regulatory framework for consortium urban operations and, mainly, an awareness of the recomposition of urban vegetation.